Quasimonogenic functions on a commutative algebra with divisors of zero - Marinov, Marin (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 1996)
Some relations between complex analysis and the function theory on algebras are considered. New equivalent conditions about quasimonogenic (in the sence of Roşculeţ) functions are given.